Power Quality Enhancement using DVR based on Ant colony Controller - Benachaiba, C.; Mazari, B.; Tandjaoui, M. N; Ahmed Mohamed, Ahmed Haidar (2016)
PI controller tuning is a difficult task under varying operating conditions. Optimal tuning of PI gains is required to get the best response of PI controllers. This paper presents the Dynamic Voltage Restorer (DVR) using ant colony optimization based PI controller (ACOPI). The simulation results demonstrate that the optimized PI controller by ant colony (ACO) presents an advantage of little response time and best control performances compared to the classical PI. The major benefit of this approach is to provide a faster DC voltage response for different voltage disturbances. The simulation results show that the approach for finding the optimal controller parameters is not easy to be implemented, but very effective in improving power quality. The total arrangement is planned, established and validated by using MATLAB–SIMULINK environment.